Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.3* The Natural Exponential Function - 6.3* Exercises - Page 452: 27



Work Step by Step

Find the limit$\lim\limits_{x \to \infty}\frac{e^{3x}-e^{-3x}}{e^{3x}+e^{-3x}}$. Thus, $\lim\limits_{x \to \infty}\frac{e^{3x}-e^{-3x}}{e^{3x}+e^{-3x}}=\lim\limits_{x \to \infty}\frac{e^{3x}(1-e^{-6x})}{e^{3x}(1+e^{-6x})}$ $=\frac{1-\lim\limits_{x \to \infty }e^{-6x}}{1+\lim\limits_{x \to \infty} e^{-6x}}$ $=\frac{1-0}{1+0}$ $=1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.